2003
DOI: 10.1007/3-540-44888-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of the Centre and Median String Problems

Abstract: Abstract. Given a finite set of strings, the median string problem consists in finding a string that minimizes the sum of the distances to the strings in the set. Approximations of the median string are used in a very broad range of applications where one needs a representative string that summarizes common information to the strings of the set. It is the case in Classification, in Speech and Pattern Recognition, and in Computational Biology. In the latter, median string is related to the key problem of Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The hardness of finding the best median for a set of points out of a (typically exponentially) large set of candidates strictly depends on the metric in consideration. For instance, the median problem has been shown to be hard for edit distance on strings [8,19], for the Kendall metric on permutations [2,9], but can be solved in polynomial time for the Hamming distance on sets (and more generally, for the ℓ 1 distance on real vectors), and for the Spearman footrule metric on permutations [9]. The general metric -median problem has also been studied in the literature; see, for example, [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…The hardness of finding the best median for a set of points out of a (typically exponentially) large set of candidates strictly depends on the metric in consideration. For instance, the median problem has been shown to be hard for edit distance on strings [8,19], for the Kendall metric on permutations [2,9], but can be solved in polynomial time for the Hamming distance on sets (and more generally, for the ℓ 1 distance on real vectors), and for the Spearman footrule metric on permutations [9]. The general metric -median problem has also been studied in the literature; see, for example, [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…In Section 2.1 (see also [21]), we have shown that CENTER STRING under Levenshtein distance is NP-complete and W[1]-hard with respect to the number of input strings, even for binary alphabet. In Section 3, we generalize these results to any weighted edit distance that satisfies a natural condition.…”
Section: Resultsmentioning
confidence: 99%
“…These results already appear in [21]. We start with the less technical of the two proofs, the one concerning CENTER STRING (Theorem 3).…”
Section: Hardness Of Center String and Median String Over Binary Alphmentioning
confidence: 90%
“…hydrophoby (for instance, this is the case in some protocols that identify similar DNA sequences [21]). In [22,23] it is shown that closest string and median string are NP-hard for finite and even binary alphabets. The existence of fast exact algorithms, when the number of input strings is fixed, is investigated in [22].…”
Section: B Rank Distancementioning
confidence: 99%